2016
DOI: 10.1063/1.4966582
|View full text |Cite
|
Sign up to set email alerts
|

Vapor-deposited alcohol glasses reveal a wide range of kinetic stability

Abstract: In situ AC nanocalorimetry was used to characterize vapor-deposited glasses of six mono- and di-alcohol molecules. Benzyl alcohol glasses with high kinetic stability and decreased heat capacity were prepared. When annealed above the glass transition temperature T, transformation of these glasses into the supercooled liquid took 10 times longer than the supercooled liquid relaxation time (τ). This kinetic stability is similar to other highly stable organic glasses prepared by vapor deposition and is the first c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 112 publications
9
45
0
Order By: Relevance
“…f BA T gðBAÞ and the T g(BA) = 168 K, 68 with T g(LA) = 50 1C and f BA = 0.05, one recovers an average T g(LA/BA) value of around 35 1C. This value is not far from room temperature especially taking into account the large polymer polydispersity leading probably to mobile parts at room temperature.…”
Section: Heterogeneous Water Invasion (Formation Of Cavities)mentioning
confidence: 62%
“…f BA T gðBAÞ and the T g(BA) = 168 K, 68 with T g(LA) = 50 1C and f BA = 0.05, one recovers an average T g(LA/BA) value of around 35 1C. This value is not far from room temperature especially taking into account the large polymer polydispersity leading probably to mobile parts at room temperature.…”
Section: Heterogeneous Water Invasion (Formation Of Cavities)mentioning
confidence: 62%
“…Predicting and controlling the properties of PVD glasses formed with different types of small organic molecules remains a fundamental challenge. In particular, intermolecular interactions seem to have a large effect on the stability of PVD films [28][29][30][31]. This was demonstrated recently by Laventure et.…”
Section: Introductionmentioning
confidence: 93%
“…However, the typical time it takes to the system to converge to this long-t w plateau, depends drastically on the final temperature. This is more clearly seen by plotting ∆(t + t w , t w )/T for t = 2 22 [i.e. the long t limit of the mean-squared displacement (MSD)] as function of t w , see Fig.…”
Section: B Growing Timescales Upon Coolingmentioning
confidence: 98%
“…Compared to their liquid-cooled counterparts, vapor-deposited glasses show higher density [16] and kinetic stability [15,17]. When these ultra-stable glasses are studied at very low temperatures, it is found that the anomalies characteristic of amorphous solids are strongly supressed [18][19][20][21][22].Many theoretical approaches to this problem are based on the study of the potential energy landscape of glassforming particle systems [13,[23][24][25][26][27][28]. These studies have suggested that glass anomalies can be interpreted in terms of glass states being not well-defined energy minima, but structured metabasins containing a collection of sub-basins separated by barriers of variable size [29,30], see Fig.…”
mentioning
confidence: 99%